Om de forskellige Midler til Hesteavlens Fremme. Foredrag, . 18de Januar 1880. - Prosch, V. (Tidsskrift for Landøkonomi, 2018)
Om de forskellige Midler til Hesteavlens Fremme. Foredrag, . 18de Januar 1880.